Manajemen Pesantren: Studi Kasus di Mahad Tahfizh Isy Karima Kecamatan Karanpandan Kabupaten Karananyar Jawa Tengah - Jatun Nur Adi Sasongko (Institut Agama Islam Negeri Purwokerto, 2018)
This study aims to comprehensively review the management of pesantren in Mahad Tahfizh Isy Karima Karangpandan Sub-district, Karanganyar Regency, Central Java. There are six aspects of pesantren management that will be studied in this research, namely curriculum, educator and educational staff, facilities and infrastructure, student, financing, and public relations. This research is a qualitative research that uses in the form of interviews, observation and documentation as data collection techniques. Stages of data analysis include data reduction, data display, and conclusion of data on aspects of pesantren management. The findings of this research are: on the curriculum side is applied the blend of curriculum 2013 with curriculum boarding school. In the aspects of management of educators and educational personnel is applied an open pattern, especially in the recruitment process carried out by publication and prioritizing competence. In the aspect of infrastructure, student and finance is implemented modern management with attention to management functions. while on the public relations aspect is prioritized the interests of stakeholders under the command of the madrasah committee.